Investor Inattention and Friday Earnings Announcements - DELLAVIGNA, STEFANO; POLLET, JOSHUA M. (Journal of Finance, 2009)
ABSTRACT Does limited attention among investors affect stock returns? We compare the response to earnings announcements on Friday, when investor inattention is more likely, to the response on other weekdays. If inattention influences stock prices, we should observe less immediate response and more drift for Friday announcements. Indeed, Friday announcements have a 15% lower immediate response and a 70% higher delayed response. A portfolio investing in differential Friday drift earns substantial abnormal returns. In addition, trading volume is 8% lower around Friday announcements. These findings support explanations of post‐earnings announcement drift based on underreaction to information caused by limited attention.